Pemanfaatan Limbah Cangkang Telur sebagai Bahan Baku Pupuk Organik Cair untuk Mendukung Pertanian Berkelanjutan di Kabupaten Siak - Ni Putu Vidya Primarista; Hasrul Hasrul; Arya Wiranata; Trisuciati Syahwardini (CV. SINAR HOWUHOWU, 2026)
This community service activity aims to utilize eggshell waste from household businesses as raw material for Liquid Organic Fertilizer (POC) to support sustainable agriculture in Siak Regency. The main problems faced by partners are high dependence on inorganic fertilizers, rising production costs, and suboptimal utilization of local organic waste. The activity was carried out through the stages of POC production, counseling, demonstrations, discussions, and product distribution to farmer groups. The POC formulation was made from eggshells, water, molasses, and EM4, then fermented for seven days. The results showed that the POC product had good physical characteristics, with changes in pH indicating optimal fermentation. The counseling and hands-on practice also increased farmers' knowledge and skills in processing eggshell waste into fertilizer that can be used independently. This program has the potential to reduce dependence on inorganic fertilizers, reduce production costs, and open up opportunities for the development of other organic waste-based products. Thus, this activity supports the implementation of sustainable agriculture and a circular economy at the community level.